(3OQGSGJ JdaRjhfjI (B:s (3GdOhQ GdJKbjaj ddJdaRjhf (B,(3GdbfhGJ GdaVGFjI GdYQHjI (B,(3WHjYI GdeYdQaI GdJdaRjhfjI (B,(3GdJdaRjhf GaGb GdeSJbHd KhQI GdGJUGdGJ (B/s - (3NVhQ,COjH s ((3OeTb (B:s (3COjH NVhQ ,s, 1998)
(3jJVef gPG GdcJGH GQHYI GHMGK JJYdb HLhGfH fXQjI h YedjI ef GdaYd GdGJUGdj GdJdaRjhfj(B. (3eGgj WHjYI GdOhQ GdJKbjaj GdPj jDOjg GdJdaRjhf ? gd jfTQ GdKbGaI h jQhLgG Ge jSWMgG h jRjagG? eGgj WHjYI GdeYQaI GdJj jbOegG GdJdaRjhf? h eGgh GdJTQjM GdLOjO ddeYQaI? h eGYdGbI Pdc HWHjYI GdJdaRjhf h HNUhUjI JLQHI GdeTGgOI ? h eGgj CKGQ JHOd WQb fSL GdGJUGd GdGLJeGYj h GdKbGaj h GdSjGSj? GdeMWGJ GdJdaRjhfjI GdaVGFjI GdYQHjI aYGdjI LOjOI gd JeJdc TNUjI eJejRI JecfgG ef JMbjb egGegG Ge GfgG JMhdJ Gdi fSN Yf GdeMWGJ GdGQVjI? h GNjQG KhQI GdGJUGdGJ h JWHjbGJgG GdYGUaI aj eLGd GdJdaRjhf HTcd ZjQ eSHhb aj eLGd GdJdaRjhf HTcd ZjQ eSHhb h GdJCKjQ GdYejb dPdc cdg Ydi cd ef GdhSjdI h GdQSGdI (B.. (3Gdi GdMO GdPj jOaY Gdi JdeS GaGb GdeSJbHd h Gdi Gdbhd HfgGjI GdYGde GdbOje GdPj fYQags
Keywords: (3KhQI GdGJUGdGJ s; (3GdJdaRjhf s; (3GdeYQaI GdJdaRjhfjI s; (3GdbfhGJ GdaVGFjI GdYQHjI s